(Fluoro)quinolones and quinolone resistance genes in the aquatic environment: A river catchment perspective. (1st September 2020) - Castrignanò, Erika; Kannan, Andrew M.; Proctor, Kathryn; Petrie, Bruce; Hodgen, Sarah; Feil, Edward J.; Lewis, Simon E.; Lopardo, Luigi; Camacho-Muñoz, Dolores; Rice, Jack; Cartwright, Nick; Barden, Ruth; et al.
Abstract: This study provides an insight into the prevalence of (fluoro)quinolones (FQs) and their specific quinolone qnrS r esistance gene in the Avon river catchment area receiving treated wastewater from 5 wastewater treatment plants (WWTPs), serving 1.5 million people and accounting for 75% of inhabitants living in the catchment area in the South West of England.. Ofloxacin, ciprofloxacin, nalidixic acid and norfloxacin were found to be ubiquitous with daily loads reaching a few hundred g/day in wastewater influent and tens of g/day in receiving waters. This was in contrast to other FQs analysed: flumequine, nadifloxacin, lomefloxacin, ulifloxacin, prulifloxacin, besifloxacin and moxifloxacin, which were hardly quantified. Enantiomeric profiling revealed that ofloxacin was enriched with the S -(−)-enantiomer, likely deriving from its prescription as the more potent enantiomerically pure levofloxacin, alongside racemic ofloxacin. While ofloxacin's enantiomeric fraction (EF) remained constant, high stereoselectivity was observed in the case of its metabolite ofloxacin- N -oxide. The removal efficiency of quinolones during wastewater treatment at 5 WWTPs utilising either trickling filters (TF) or activated sludge (AS), was compound and wastewater treatment process dependent, with AS providing better efficiency than TF. The qnrS resistance gene was ubiquitous in wastewater. Its removal was WWTP treatment process dependent with TF performing best and resulting in significant removal of the gene (from 28 to 75%). AS underperformed with only 9% removal in the case of activated sludge and actual increase in the gene copy number within sequencing batch reactors (SBRs). Interestingly, the data suggests that higher removal of antibiotics could be linked with high prevalence of the gene (SBR and WWTP E) and vice versa, low removal of antibiotic is correlated with lower prevalence of the gene in wastewater effluent (TF, WWTP B and D). This is especially prominent in the case of ofloxacin and could indicate that AS might be facilitating antimicrobial resistance (AMR) prevalence to higher extent than TF. Wastewater-based epidemiology (WBE) was also applied to monitor any potential misuse ( e.g. direct disposal) of FQs in the catchment. In most cases higher use of antibiotics with respect to official statistics ( i.e. ciprofloxacin, ofloxacin) was observed, which suggests that FQs management practice require further attention. Graphical abstract: Image 1 Highlights: Spatiotemporal evaluation of the prevalence of FQs and qnrS in a river catchment. Strong correlation between daily loads of FQs and qnrS observed. FQs and ARG loads directly proportional to the size of a population served by WWTPs. Higher removal of FQs linked with higher prevalence of qnrS gene. WBE: Higher use of antibiotics than official statistics observed.